Spherical-shaped ice particle production by spraying water in a vacuum chamber - Shin, HT; Lee, YP; Jurng, J (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
A theoretical and experimental study was performed to examine the water spray evaporation method for ice particle production. The conditions for the formation of ice particles were investigated theoretically by the diffusion-controlled evaporation model. The prediction by the model was proved to agree relatively well with experiments. The production of cold storage heat will increase almost proportionally to the number of spray nozzles because no substantial difference was found in the mean droplet size of the overlapped sprays from twin nozzles. Finally, based on the results, the vacuum chamber was designed, and spherical ice particles of size below 300 mu m were experimentally obtained by spraying water droplets of ambient temperature in the vacuum chamber where pressure is maintained below the freezing point of water. From the experiment for producing ice particles, it was found that the spray flow rate influences the performance of the system mon than the position of spray nozzle. (C) 2000 Elsevier Science Ltd. All rights reserved.